2022
DOI: 10.3390/jcm11195973
|View full text |Cite
|
Sign up to set email alerts
|

Is Primary Bone Marrow Edema of the Knee Associated with Thyroid Disorders? A Retrospective Clinical Study

Abstract: Primary bone marrow edema (BME) of the knee is still an elusive condition. This retrospective study was undertaken to gain insight into its characteristic features. The records of 48 patients with primary BME of the knee diagnosed by magnetic resonance imaging were reviewed. Demographic data, medical history, current medications, pain type, smoking and drinking habits, allergies, occupation, sports practiced, environmental factors, and life events predating symptom onset were examined. Data analysis demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Tokgoz et al reported that greater bone mineral density (BMD) can delay the progression of knee osteoarthritis (KOA) 44 . The impact of thyroid-related hormone levels on bone tissue has long been studied by scholars 45 , 46 , and among these impacts, TH and TSH have positive regulatory and maintenance effects on bone development 47 , 48 . High TH levels in hyperthyroidism patients lead to an increase in the bone turnover rate and an imbalance in the proportion of bone resorption and bone formation processes 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Tokgoz et al reported that greater bone mineral density (BMD) can delay the progression of knee osteoarthritis (KOA) 44 . The impact of thyroid-related hormone levels on bone tissue has long been studied by scholars 45 , 46 , and among these impacts, TH and TSH have positive regulatory and maintenance effects on bone development 47 , 48 . High TH levels in hyperthyroidism patients lead to an increase in the bone turnover rate and an imbalance in the proportion of bone resorption and bone formation processes 49 .…”
Section: Discussionmentioning
confidence: 99%